The Impact of Applying the Expected Credit Loss Model on Bank Profitability An Applied Study on Private Traditional Banks Listed on the Damascus Securities Exchange (Latakia University (formerly Tishreen)Journal for Research and Scientific Studies - Economic and Legal Sciences Series, 2026)
This study examines the effect of expected credit losses across the three IFRS 9 stages on the profitability of conventional banks, while introducing two control variables, bank size and exchange rate, to improve estimation accuracy and isolate the net effect of each stage. The analysis is based on panel data for a sample of listed conventional banks over the period 2019–2023. Fixed-effects panel models were estimated after conducting the appropriate model selection tests, with corrected standard errors to address possible heteroskedasticity. The findings show that expected credit losses recognized in Stage 1 have a positive and statistically significant effect on return on assets, suggesting that early loss recognition is associated with more prudent banking behavior and supports the relative stability of financial performance. The results further indicate that the effect of Stage 2 expected credit losses is negative in sign but not statistically decisive after controlling for bank size and exchange rate, implying that banks were generally able to absorb this category of credit risk without a substantial deterioration in profitability. By contrast, Stage 3 expected credit losses exhibit a strong negative and statistically significant impact on profitability, reflecting the direct burden of actual credit deterioration through higher provisioning and lower returns on assets. The results also show that bank size has a positive effect on profitability, whereas the exchange rate exerts a negative effect. Diagnostic tests confirm the adequacy of the estimated models and support the reliability of the empirical findings.
Keywords: Expected credit losses, IFRS 9, Bank profitability, Bank size, Exchange rate.